Biology is the root of variability: cautionary tales in Caenorhabditis elegans biology. (24th May 2019) - Pho, Kim B.; MacNeil, Lesley T.
Abstract : Reproducibility is critical for the standardization, interpretation, and progression of research. However, many factors increase variability and reduce reproducibility. In Caenorhabditis elegans research, there are many possible causes of variability that may explain why experimental outcomes sometimes differ between laboratories and between experiments. Factors contributing to experimental variability include the genetic background of both C. elegans and its bacterial diet, differences in media composition, intergenerational and transgenerational effects that may be carried over for generations, and the use of chemicals or reagents that may have unexpected consequences. This review summarizes sources of variability in C. elegans research and serves to identify laboratory practices that could influence reproducibility.